PENGARUH AKUNTANSI MANAJEMEN DAN FINANCIAL KNOWLEDGE TERHADAP PENGAMBILAN KEPUTUSAN MANAJEMEN PADA SEMUA BANK DI KABUPATEN KEPULAUAN ARU - Magdalena Kalorbobir, Yohana (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the influence of management accounting and financial knowledge on management decision-making in all banks in the Aru Islands Regency. Given the unique characteristics of the archipelago and challenges in infrastructure, human resources, and financial inclusion, the quality of managerial decision-making is a critical factor for the sustainability and performance of local banking institutions. This study uses a quantitative approach with a sample of 30 respondents from top, middle, and first-line management levels in all banks in the Aru Islands Regency. Data collection was conducted through a Likert-based questionnaire, and data analysis used multiple linear regression with the help of SPSS 26. The results showed that simultaneously, management accounting and financial knowledge significantly influence management decision-making (F = 41.633; p = 0.000; R² = 0.828). Partially, management accounting has a positive and significant effect (β = 0.749; t = 5.690; p = 0.000), as does financial knowledge (β = 0.280; t = 2.387; p = 0.025). These findings indicate that improving the quality of management accounting systems and increasing managers' financial literacy significantly increase the effectiveness of strategic and operational decision-making in banking institutions. The implications of this study provide recommendations for increasing managerial capacity and strengthening banking governance in remote areas